Air Pollution From Forest and Vegetation Fires in Southeast Asia Disproportionately Impacts the Poor. (2nd September 2021) - Reddington, Carly L.; Conibear, Luke; Robinson, Suzanne; Knote, Christoph; Arnold, Stephen R.; Spracklen, Dominick V.
Abstract: Forest and vegetation fires, used as tools for agriculture and deforestation, are a major source of air pollutants and can cause serious air quality issues in many parts of Asia. Actions to reduce fire may offer considerable, yet largely unrecognized, options for rapid improvements in air quality. In this study, we used a combination of regional and global air quality models and observations to examine the impact of forest and vegetation fires on air quality degradation and public health in Southeast Asia (including Mainland Southeast Asia and south‐eastern China). We found that eliminating fire could substantially improve regional air quality across Southeast Asia by reducing the population exposure to fine particulate matter (PM2.5 ) concentrations by 7% and surface ozone concentrations by 5%. These reductions in PM2.5 exposures would yield a considerable public health benefit across the region; averting 59, 000 (95% uncertainty interval (95UI): 55, 200–62, 900) premature deaths annually. Analysis of subnational infant mortality rate data and PM2.5 exposure suggested that PM2.5 from fires disproportionately impacts poorer populations across Southeast Asia. We identified two key regions in northern Laos and western Myanmar where particularly high levels of poverty coincide with exposure to relatively high levels of PM2.5 from fires. Our results show that reducing forest and vegetation fires should be a public health priority for the Southeast Asia region. Plain Language Summary: Forest and vegetation fires, used for forest clearance and agriculture in Southeast Asia, are a major source of air pollutants and can cause serious air quality issues. In this study, we used computer models and measurements of air pollution to examine the effect of forest and vegetation fires on air quality degradation and public health in Southeast Asia (including Mainland Southeast Asia and south‐eastern China). We found that preventing these fires could substantially improve regional air quality and yield a considerable public health benefit across the region; avoiding around 59, 000 premature deaths every year. Furthermore, our analysis of poverty data suggests that particulate pollution from fires disproportionately impacts poorer populations across Southeast Asia. Our results show that reducing forest and vegetation fires should be a public health priority for the Southeast Asia region. Key Points: Eliminating forest and vegetation fires could substantially improve regional air quality in Mainland Southeast Asia Reducing exposure to particulate and ozone pollution from fires would yield a considerable public health benefit across Southeast Asia Particulate air pollution from fires disproportionately impacts poorer populations across Southeast Asia